Exploring the Potential of Lactoferrin in Neonatology and Obstetrics - Promising Advancements for Maternal and Infant Health - Bialic, Kinga; Bialic, Artur; Bakalarczyk, Rafał; Majewski, Paweł; Bednarz, Lucjan; Szala-Czerwonka, Karolina; Woś, Natalia; Rejmer, Adrian; Rojek, Katarzyna; Wijas, Karolina (Journal of Education, Health and Sport, 2023)
Introduction and purpose: Lactoferrin (Lf), a glycoprotein found in body fluids, plays a key role in many of the biological mechanisms that occur in the human body. Over the years, more and more studies have contributed to the expansion of the clinical applications of lactoferrin. In this article, we want to focus on using lactoferrin in Neonatology and Obstetrics. The applications of lactoferrin in obstetrics continue to expand, some of which include the prevention of preterm delivery (PTD) and anaemia in pregnant women. Lf also helps to reduce the incidence of necrotizing enterocolitis and sepsis in newborns by mobilising the immune system and participating in the defence against pathogens and has been under investigation as a potential therapeutic agent for genital infections. The aim of this review is to summarise the current state of knowledge, regarding lactoferrin’s broad spectrum of action and to highlight its potential therapeutic applications in these contexts. State of knowledge: This article aims to review the current knowledge on the properties of the lactoferrin and its applications in medicine, especially neonatology and obstetrics. Studies available in the PubMed and Google Scholar databases were included in the analysis. Conclusion: While lactoferrin shows promise in improving neonatal and maternal health, additional research is required to fully understand its precise mechanisms of action and optimise its use as a therapeutic agent. There is also a need for further studies to assess the safety and efficacy of lactoferrin in a variety of patient populations. Despite the challenges, lactoferrin continues to be an intriguing subject of scientific research, with potential therapeutic benefits in various medical fields.